Impact of Mass on Rolling Resistance Power Loss in Photovoltaic Electric Vehicles Under Sahelian Conditions - Sokhna, Sidy Mactar; Diarra, Sory; Ali, Mohamed El Amine Ait; Faye, Souleye; Sambou, Vincent; Agouzoul, Mohamed; Thierno Ass Abdoul LY (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
The vehicle under examination is an electric generator powered by a photovoltaic source. A proportion of the energy is employed to propel the vehicle, which has a maximum speed of 35.7 km/h and a mass of 300 kg, over a distance of 70 km. Another portion of the energy is captured and converted into electricity for domestic use. The vehicle is equipped with electric motors, with a rated power of 3,000 W and a voltage of 48 V, which are installed in the rear wheels for propulsion purposes. Some of the power is lost due to resistances such as air resistance, rolling resistance, and gradient. These resistances must be overcome during the journey, with rolling resistance accounting for the majority of the resistance. An initial experiment was conducted using an electric vehicle protocol to collect data, which enabled the collection of data on different speeds and the corresponding starting powers. The data were subsequently employed to ascertain the rolling resistance value through the utilisation of a resolution method that considers variables such as tyre inflation pressure, velocity, and vehicle mass. This method involves the calculation of a coefficient, designated the traction coefficient, which is a function of the local deformation of the tyre in response to wheel load. The power dissipated by rolling resistance can be determined from the data. Using MATLAB, the variations in power dissipated by rolling resistance can be visualised. The vehicle is driven on an asphalt concrete surface. This study demonstrates the behaviour of electric vehicles and enables the determination of their performance under driving conditions, taking into account rolling resistance, mass, and speed.